2018
DOI: 10.5530/jyp.2018.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality among Individuals with Tuberculosis and Human Immunodeficiency Virus Coinfection at a Reference Center in Southeastern Brazil: A Retrospective Cohort Study

Abstract: Background: Tuberculosis (TB) remains an important cause of morbidity, the leading cause of death in patients with human immunodeficiency virus (HIV) infection, and a challenge to global public health. This study aimed to analyze the predictors associated with mortality among individuals coinfected with TB/HIV at a reference center in southeastern Brazil. Method: This retrospective cohort study used the data obtained from clinical records and information systems from 2007 to 2014. The data were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Thus, a one year increase in the age of TB patients increased the risk of death by 2.2%. This result implies that the age of patients was directly associated with the mortality of TB patients [ 35 , 36 , 37 ]. Similarly, [ 38 ] showed that mortality due to TB was indirectly associated with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a one year increase in the age of TB patients increased the risk of death by 2.2%. This result implies that the age of patients was directly associated with the mortality of TB patients [ 35 , 36 , 37 ]. Similarly, [ 38 ] showed that mortality due to TB was indirectly associated with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the fact that in rural areas, the patients may faced with lack of balanced diet and proper adherence to medication because of limited accessibility of ART clinic settings or health facilities as compared to urban and low level of patients' awareness about the treatment. This indicates that the exposure of status of TB on HIV patients were high in rural area [22].…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, a Chinese study found that not using ART was a risk factor for TB 31 . Other studies have shown that late-onset of ART 32 or not doing it 33 were risk factors for mortality in cases of coinfection.…”
Section: Discussionmentioning
confidence: 96%